Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12888-017-1412-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prospective pharmacogenetic testing in the treatment of major depressive disorder: results of a randomized, double-blind clinical trial

Abstract: BackgroundA 12-week, double-blind, parallel, multi-center randomized controlled trial in 316 adult patients with major depressive disorder (MDD) was conducted to evaluate the effectiveness of pharmacogenetic (PGx) testing for drug therapy guidance.MethodsPatients with a CGI-S ≥ 4 and requiring antidepressant medication de novo or changes in their medication regime were recruited at 18 Spanish public hospitals, genotyped with a commercial PGx panel (Neuropharmagen®), and randomized to PGx-guided treatment (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
152
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(157 citation statements)
references
References 43 publications
(41 reference statements)
2
152
0
3
Order By: Relevance
“…Multiple studies have recently been published illustrating the clinical value of multigene pharmacogenetic panels when treating patients with depression. At least four rigorous studies have shown significantly better treatment outcomes for major depressive disorder with pharmacogenomic guidance compared with the standard clinical approach .…”
Section: Antidepressant Selectionmentioning
confidence: 99%
“…Multiple studies have recently been published illustrating the clinical value of multigene pharmacogenetic panels when treating patients with depression. At least four rigorous studies have shown significantly better treatment outcomes for major depressive disorder with pharmacogenomic guidance compared with the standard clinical approach .…”
Section: Antidepressant Selectionmentioning
confidence: 99%
“…1 It was the second article 2 on this topic within a month, coming from the same country, confirming for us how useful pharmacogenetic testing can be in our daily practice. Reading these articles reminded us of a third, where we had the pleasure to revisit the process of clinical equipoise, 3 something that we believe should be an essential part of the modern model of psychiatric practice for treatment resistance.…”
Section: To the Editormentioning
confidence: 74%
“…47 To appeal to the request for evidence demonstrating clinical utility, the collective clinical utility for a subset of genes in the PGx-Passport (Table S1) is being assessed in a cluster randomized controlled trial including 8,100 patients across healthcare institutions in 7 European countries. 21 Several promising studies indicate the (cost-)effectiveness of PGx panel-based testing on healthcare utilization in psychiatry and polypharmacy, [22][23][24]26 where observed cost savings ranged from $218 23 to $2,778 48 per patient. Others have modeled the cost-effectiveness of one-time genetic testing to minimize a lifetime of adverse drug reactions, and concluded an incremental cost-effectiveness ratio of $43,165 per additional life year and $53,680 per additional quality-adjusted life year, and, therefore, cost-effective.…”
Section: Determining This Variant Allele May Be Less Relevant (But Nomentioning
confidence: 99%
“…Logistics and cost‐effectiveness are, therefore, optimized when delivered in a pre‐emptive panel‐based approach; pharmacotherapy does not have to be delayed, awaiting single‐gene testing results and costs for genotyping are minimized, as marginal acquisition costs of testing and interpreting additional pharmacogenes is near‐zero . Although a sufficiently powered and well‐designed study assessing the (cost‐)effectiveness of pre‐emptive PGx testing is yet to be concluded, a number of small randomized observational studies indicate promising clinical utility of PGx panel testing . Another important challenge hampering adoption of pre‐emptive panel testing is the lack of standardization regarding variants included in such panels.…”
mentioning
confidence: 99%
See 1 more Smart Citation